Lower extremity power generation strategies used by elite athletes during the take-off phase of the long jump - Costa, K. E.; McNitt-Gray, J. L. (1999)
In conclusion, a significant relationship was found between positive work done at the hip and large increases in TBCM vertical velocity during the take-off phase of the long jump. Results indicate that maintaining a small negative or near zero knee NJM leads to a positive hip NJM and positive work done at the hip.